Fair Cost Sharing Auction Mechanisms in Last Mile Ridesharing - NGUYEN, Duc Thien (Institutional Knowledge at Singapore Management University, 2013)
With rapid growth of transportation demands in urban cities, one major challenge is to provide efficient and effective door-to-door service to passengers using the public transportation system. This is commonly known as the Last Mile problem. In this thesis, we consider a dynamic and demand responsive mechanism for Ridesharing on a non-dedicated commercial fleet (such as taxis). This problem is addressed as two sub-problems, the first of which is a special type of vehicle routing problems (VRP). The second sub-problem, which is more challenging, is to allocate the cost (i.e. total fare) fairly among passengers. We propose auction mechanisms where we allow passengers to submit their willing payments. We show that our bidding model is budget-balanced, fairness-preserving, and most importantly, incentive-compatible. We also show how the winner determination problem can be solved efficiently. A series of experimental studies are designed to demonstrate the feasibility and efficiency of our proposed mechanisms.